HUBUNGAN ASUPAN GIZI DAN AKTIVITAS FISIK DENGAN INDEKS MASSA TUBUH MENURUT UMUR (IMT/U) PADA ANAK JALANAN (Studi Kasus Rumah Pintar Bang Jo PKBI Jawa Tengah di Kawasan Pasar Johar Kota Semarang Tahun 2018) - Nurul Aindina Madaliana; M. Zen Rahfiludin; Ronny Aruben (Jurnal Kesehatan Masyarakat (Undip), 2018)
Street children are children aged 5-18 years who have activities and physical work is quite tiring. Most of the street children have low nutrient intake, if left continuously will adversely affect on nutritional status.The objective of this study is to analyze the relationship between of nutrient intake and physical activity with the Body Mass Index for Age of street children. This type of research is quantitative research using cross sectional approach. The population of this study was the 73 street children in Rumah PintarBangJo and the sample in this study were 42 street children selected with purposive sampling method. Data were analyzed using Pearson Product Moment test for normal distributed data, Rank Spearman test for abnormally distributed data and Chi Square test for nominal scale data. The results of this study age of repondents at most in 5-12 year age group. The sexes of both male and female respondents were the same (50%) and the education status of most respondents with primary school (57,1%). Most of the energy intake, carbohydrate intake and protein intake of the respondents included in the category of good, but the fat intake of many respondents included in the category less.  The mean and standard deviation of energy intake of respondents were 1301 ± 802.1 kcal per day.  The mean and standard deviation of carbohydrate intake of respondents were 212.8 ± 120 g per day. The mean and standard deviation of fat intake of respondents were 39.1 ± 28.9 g per day. The mean and standard deviation of protein intake of respondents were 48.9 ± 26.2 g per day. The nutritional status of the respondents was mostly in the normal category (57,1%), followed by obesity (14.3%), Thinness (11,9%), Severe thinness (9,5%) and overweight (7,1%).Most children have a history of infections (54,8%) and have a light physical activity (63,3%). There were correlation between age (p = 0,039),  energy intake (p = 0.034), fat (p = 0.005,  protein (p = 0.047), history of infection (p = 0,049) and physical activity (p = 0,007) with Body Mass Index for Age of street children. There were no correlation between gender (p = 0,533), education (p = 0,780) and carbohydrate intake (p = 0.121) with Body Mass Index for Age of street children.